Sinus Histiocytosis With Massive Lymphadenopathy (Rosai Dorfman Disease): Diagnostic and Treatment Modalities for this Rare Entity Revisited. Issue 4 (May 2018) - Averitt, Andrew W.; Heym, Kenneth; Akers, Lauren; Castro-Silva, Fernando; Ray, Anish
Abstract : Rosai-Dorfman disease, also known as sinus histiocytosis with massive lymphadenopathy is a rare non-Langerhans' cell histiocytic disease resulting from the proliferation and accumulation of sinus histiocytes within lymph nodes. Extranodal involvement frequently occurs, which increases the morbidity and mortality of the disease. There is no clear consensus with regard to the most effective diagnostic and treatment modalities. This report will focus on the diagnostic imaging, treatment, and outcomes for 3 cases of Rosai-Dorfman disease. Imaging has typically utilized computed tomography (CT)/magnetic resonance imaging to detect extranodal involvement. However, the addition of fluorodeoxyglucose positron emission tomography/CT scans has shown value in identifying lesions unidentified or ambiguous on other modalities. Fluorodeoxyglucose positron emission tomography/CT detected disease involvement in 2 instances either not reported or not felt to be significant on correlative CT imaging. Areas of involvement included the stomach/liver in case 1, and the paranasal sinus in case 3. In addition, previously utilized chemotherapy regimens have not consistently displayed regression of the disease, which lends credence to the pursuit of more successful treatment. Notably, Clofarabine has shown promise in its use against histiocytic disorders. Our study concluded that Clofarabine demonstrates the ability to decrease lesion size and should be considered as an effective chemotherapeutic treatment method.